Lnc-ITM2C-1 and GPR55 are Proviral Host Factors for Hepatitis C Virus - Hu, Pan; Justus Liebig University Giessen (My University, 2019)
Multiple host factors are known to play important roles in Hepatitis C Virus (HCV) replication, in immune responses induced by HCV infection, or in processes that facilitate virus escape from immune clearance, while yet only few studies examined the contribution of long non-coding RNAs (lncRNAs/lncRs). Using microarrays, we identified lncRNAs with altered expression levels in HCV replicating Huh-7.5 hepatoma cells. Of these, lncR 8/Lnc-ITM2C-1 was confirmed by quantitative real-time polymerase chain reaction (qRT-PCR) to be upregulated early after HCV infection. Nucleus/cytoplasm fractionation showed a preferential nuclear localization of lncR 8. Expression of lncR 8 in Huh-7.5 could be largely repressed by GapmeRs (GmRs). After suppressing the expression of lncR 8, HCV RNA and protein were downregulated, confirming a positive correlation between lncR 8 expression and HCV replication. LncR 8 knockdown in Huh-7.5 cells reduced mRNA expression level of the neighboring gene G protein-coupled receptor 55 (GPR55) at early times, and leads to increased levels of several interferon stimulated genes (ISG) including interferon stimulated gene 15 (ISG15), MX dynamin like GTPase 1 (Mx1) and interferon induced transmembrane protein 1 (IFITM1). Importantly, the effect of lncR 8 on ISGs and GPR55 precedes its effect on HCV replication. Furthermore, knockdown of GPR55 mRNA induces ISG expression, providing a possible link between lncR 8 and ISGs. We conclude that HCV induces lncR 8 expression, while lncR 8 indirectly favors HCV replication by stimulating expression of its neighboring gene GPR55, which in turn downregulates expression of ISGs. The latter fact is also consistent with a pro-inflammatory role of GPR55. These events may contribute to the failure of cells to eliminate ongoing HCV infection.
Keywords: ddc:610